Airbus A380: An icon of change for Malaysia Airlines - Norizan, Nur Hazira; Lee, Chun Han; Abdul Malik, Intan Nurul Afiqah; Sabar, Rohafiz (2012)
The aims of the study are to determine the purpose of buying Airbus A380 by Malaysia Airlines (MAS) and the effect of Airbus A380 to the Malaysia aircraft industry. The research was conducted by distributing questionnaires to 50 students of UUM for measures the impact of A380 to Malaysia Airlines (MAS).The relationships between the independent and dependent variables were identified by using the descriptive and inferential analysis. There is enough evidence prove that there are no significant differences between student’s gender and factors of student’s preferable aircraft and there are no significant differences between student’s gender and function of A380 in affect the efficiency of MAS.